Effects of Cold Extrusion on the Mechanical Properties of Scrapped Copper Coil - Olawore A. S.; Oladosu K. O.; Sadiq T. O.; Ahmed M.; Adesope W. A. (Журнал інженерних наук)
The recycling of copper coil into finished products via sand casting with subsequent cold extrusion was investigated. This paper examined the effects of cold extrusion on the mechanical properties of the scrapped copper coil using a locally manufactured extruder with a conventional face die. The mechanical properties tested on the extrudates are limited to hardness, tensile, and compressive strength. The results reveal that the hardness of extruded copper of 11.10 mm and 11.45 mm improved significantly by 39 % and 41 %, respectively, compared with respective non-extruded copper. The compressive and tensile strength increases by 42 % and 22 %, respectively, for 11.10 mm extruded copper compared with the corresponding non-extruded copper. Also, the elongation of the extruded copper of 11.10 mm and 11.45 mm increases by 33 % and 34 %, respectively. It was deduced that the extruded copper is more ductile than the non-extruded copper. The micrograph reveals that grains in non-extruded copper are relatively coarse and nonuniform with voids, but fine and relatively uniform grains are obtained in extruded copper. The grains are refined during cold extrusion, and voids and dislocations are reduced significantly.